2019
DOI: 10.1039/c8fd00204e
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy and nanocalorimetry of hydrated magnesium ions [Mg(H2O)n]+, n = 20–70: spontaneous formation of a hydrated electron?

Abstract: Hydrated singly charged magnesium ions [Mg(H 2 O) n ] + are thought to consist of an Mg 2+ ion and a hydrated electron for n > 15. This idea is based on mass spectra, which exhibit a transition from [MgOH(H 2 O) nÀ1 ] + to [Mg(H 2 O) n ] + around n ¼ 15-22, black-body infrared radiative dissociation, and quantum chemical calculations. Here, we present photodissociation spectra of size-selected [Mg(H 2 O) n ] + in the range of n ¼ 20-70 measured for photon energies of 1.0-5.0 eV. The spectra exhibit a broad abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 71 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…Recently, our group also studied the electronic spectra of Mg + (H 2 O) n clusters in the n = 1-5 and n = 20-70 size regime. 20,21 The electronic spectra of transition metal ion-water complexes were also studied by Metz and co-workers, investigating the Ni + (H 2 O) and Co + (H 2 O) complex, 22,23 and Abate et al, studying the Zn + (H 2 O) complex. 24 Structural trends and solvation evolution can be determined by employing infrared (IR) spectroscopy, and has been used extensively by many groups to investigate the structural isomers of metal ion-water complexes as a function of cluster size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, our group also studied the electronic spectra of Mg + (H 2 O) n clusters in the n = 1-5 and n = 20-70 size regime. 20,21 The electronic spectra of transition metal ion-water complexes were also studied by Metz and co-workers, investigating the Ni + (H 2 O) and Co + (H 2 O) complex, 22,23 and Abate et al, studying the Zn + (H 2 O) complex. 24 Structural trends and solvation evolution can be determined by employing infrared (IR) spectroscopy, and has been used extensively by many groups to investigate the structural isomers of metal ion-water complexes as a function of cluster size.…”
Section: Introductionmentioning
confidence: 99%
“…48 These studies showed that hydrated monovalent zinc ions can be oxidized by suitable reactants, but the details of the reactions and their cluster size-dependence can be quite complex. The question arises whether hydrated electrons are formed in sufficiently large clusters, similar to Mg + (H 2 O) n , 21 however an insertion to form HZnOH + does not seem plausible, given the lack of H/D exchange in the D 2 O experiment. 45 To shed more light on these reactions, the structural properties of Zn + (H 2 O) n , with n r 35, are probed by infrared spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hydrated metal ions M + (H 2 O) n , M=Mg, Cr, Co, pick up exactly one CO 2 molecule, indicating that electron transfer from the metal to carbon dioxide takes place . In the case of magnesium, the electron is already present in the hydration shell, detached from the metal center, as recently confirmed by electronic spectroscopy of Mg + (H 2 O) n …”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68] In the case of magnesium, the electron is already present in the hydration shell, detached from the metal center, as recently confirmed by electronic spectroscopy of Mg + (H 2 O) n . [69] For the structural analysis of hydrated metal ions M(H 2 O) n (M = Li + ,N a + ,M g + ,M g 2 + ,A l + ,C a 2 + ,C o + ,C o 2 + ,C u + ,A g + , Cs + ,B a 2 + ,T m 3 + ,L a 3 + ), as eries of infrared photodissociation studies are available. [70][71][72][73][74][75][76][77] Pure cationic cobalt clusters Co n + Ar were investigated spectroscopicallyb ya rgon tagging.…”
Section: Introductionmentioning
confidence: 99%